Formulating Marine Tourism Service Standards for Soetan Island, Pesisir Selatan Regency - Putra, Rahmat Eka; Rivai, Harif Amali; Syafrizal, Syafrizal; Adrianto, Fajri (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Standardizing marine tourism services is essential to ensure the quality and safety of visitors. With standardization, marine tourism service providers can ensure that all aspects of services, such as equipment, facilities, and human resources, meet the established criteria. This will increase visitor confidence and reduce the risk of accidents. In addition, standardization also helps improve the efficiency and effectiveness of services so that visitors can enjoy a better tourism experience. Standardization of marine tourism services also has a positive impact on the local economy and environment. With increasing service quality, tourists will be more likely to return and recommend the destination, thereby increasing local economic income. Therefore, we must implement and strictly monitor the standardization of marine tourism services to maintain the quality and sustainability of the marine environment. A standard operating procedure (SOP) document embodies the realization of service standardization. We prepared the SOP through a Focus Group Discussion (FGD) with Soetan Island management. Four FGDs took place, leading to the creation of four SOP documents for Soetan Island's marine tourism services. This SOP document is a guide for Soetan Island Tourism Management in providing services to tourists, which support the realisation of decent work and service that leads to the economic growth.